Child Weaning Practices among Selected Urban Slums of Dhaka City, Bangladesh (Journal of Scientific Research, 2017)
When a baby reaches 4-6 months, milk alone is not sufficient to meet the increased nutritional needs of the baby. Weaning is the process by which a baby slowly gets used to eating family or adult foods along with breast milk. The aim of the study was to assess the weaning practices in the selected urban slums of Dhaka city, Bangladesh among male and female children in the age group of 6 months to 1 year by random sampling. It revealed that 54% infants were fed breast milk and 38.5% infants were fed honey as their first food. About 94.5% infants were given breast milk within (1-24) h, 5% within (24-48) h and 0.5% within (48-72) h. As a weaning food majority of the respondents (39%) used khichuri, 24.5% used mashed potato/banana, 19% used powdered rice, 17% used suzi and 0.5% used others. 33% respondents had no knowledge about nutritious food. About 54%, 38.5%, 6.5% and 1.0% mothers fed their baby breast milk, honey, sugar and other food items respectively just after birth. The studied population group is not only poverty stricken, but also has poor knowledge, attitude and practice on health, hygiene, nutrition and nutritious food.